(untitled) (Bangladesh Journal of Agricultural Research, 2012)
The study analyzed the risks involved in fruit and vegetable farming in Osun state, Nigeria. Specifically, the study examined the risk attitude of farmers, factors influencing risk attitude as well as farmers perception on major sources of production and market risks. The study was based on a survey of 150 farmers, comprising 75 predominantly fruit and vegetable farmers, respectively, and covering 12 communities within the six agro-ecological zones in the state. Data were collected using a well structured questionnaire. Descriptive statistics, discriminant analysis and KruskalWallis ranking analysis were used in the study. The study revealed that the average age of the fruit and vegetable respondent was 58.5 and 40.1, respectively, with the male respondents outnumbering the females in each case. The average year of experience was 30.8 and 15.3 for fruit and vegetable respondent, respectively. An average area of (5.36 and 2.21) ha was cultivated by the fruit and vegetable farmers, while orange and okra are the most widely grown fruit and vegetable crops. Damage by pest and disease, traditional methods of farming and weather dependency were the most perceived sources of production risk by the fruit and vegetable farmers. Perishability of produce, low price of produce, poor product handling and packaging as well as exploitation by middlemen were the most perceived sources of market risk. The study also revealed that maintaining good relationship with traders, selling at low prices due to perishability, selling within the locality and non-farm businesses were the major risk management strategies employed by the farmers. Based on the study findings, it is recommended that introduction of a more comprehensive agricultural insurance scheme and introduction of improved technology can ameliorate the effect of risks on fruit and vegetable farmers. Also, public intervention can facilitate better risk management through improved information system. Bangladesh J. Agril. Res. 37(3): 473-491, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12125